2018
DOI: 10.1007/s00405-018-4903-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Dysphonia Severity Index and Acoustic Voice Quality Index measures in differentiating normal and dysphonic voices

Abstract: The outcomes of the present study indicate comparable results between DSI and AVQI with a high level of validity to discriminate between normal and dysphonic voices. However, a higher level of accuracy was yielded for AVQI as a correlate of auditory perceptual judgment suggesting a reliable voice screening potential of AVQI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 40 publications
1
6
0
3
Order By: Relevance
“…On the other hand, continuous speech is more representative of daily speech and, therefore, can be considered to be more 'ecologically valid' [6]. Several studies in the last decade already demonstrated the robust diagnostic accuracy of AVQI [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], its consistent and high concurrent validity [5,[7][8][9][10][11][12][13][14][15][16][17]19,[21][22][23][24][25] and its high sensitivity to voice changes across voice therapy [8,12,16,18,21]. Furthermore, studies validating the use of AVQI in different languages showed diagnostic accuracy according to inter-language phonetic differences [9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, continuous speech is more representative of daily speech and, therefore, can be considered to be more 'ecologically valid' [6]. Several studies in the last decade already demonstrated the robust diagnostic accuracy of AVQI [5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], its consistent and high concurrent validity [5,[7][8][9][10][11][12][13][14][15][16][17]19,[21][22][23][24][25] and its high sensitivity to voice changes across voice therapy [8,12,16,18,21]. Furthermore, studies validating the use of AVQI in different languages showed diagnostic accuracy according to inter-language phonetic differences [9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%
“…However, DSI performed better than AVQI related to nearly all outcomes of diagnostic accuracy (i.e., sensitivity, A ROC , LR+, LR−, and CCR). According to the evaluation of objective overall voice quality, several studies confirmed the assumption that AVQI is a more valid measurement than DSI . With smoothed cepstral peak prominence and shimmer as part of the constituents, the AVQI model is primarily related to periodicity prominence and therefore presumed to solely measure voice quality.…”
Section: Discussionmentioning
confidence: 98%
“…According to the evaluation of objective overall voice quality, several studies confirmed the assumption that AVQI is a more valid measurement than DSI. 36,50 With smoothed cepstral peak prominence and shimmer as part of the constituents, the AVQI model is primarily related to periodicity prominence 51 and therefore presumed to solely measure voice quality. In contrast, the DSI incorporates not only a voice quality-related measure (i.e., jitter percent) but also three measures more related to vocal performance and functioning (i.e., MPT, Fhigh and Ilow).…”
Section: Discussionmentioning
confidence: 99%
“…En todos los casos, la severidad de una disfonía da cuenta del grado de alteración que tiene una voz en relación con todos los procesos fisiológicos involucrados con la producción del sonido [11,12]. Para el clínico es importante determinar tal nivel de severidad, a fin de establecer un programa con el conjunto de ejercicios más apropiado para la rehabilitación [12,13].…”
Section: Introductionunclassified